CURRENT STATE OF BANK LENDING IN UKRAINE - NIKOLCHUK, Yuliia; SHEVCHUK, Alona (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The relevance of the chosen topic of scientific research is determined by the fact that the gradual stabilization of the banking system and its adaptation to wartime realities give hope for the successful continuation of active lending to the population and business. At the same time, it would be premature to claim that the banking system as a whole and its individual credit organizations have finally overcome the consequences of the crisis and that their further development is not related to possible financial shocks. Factors that can significantly influence the state of the banking system as a whole and of a specific commercial bank in particular retain their importance. The purpose of the article is to study the current state of bank lending in Ukraine, identify current problems and outline possible ways to solve them. The current state of bank lending in Ukraine is considered. The dynamics of loans were analyzed in terms of borrowers, types of economic activity and lending currencies. Common factors that negatively affect the development of bank lending are identified. Particular attention is paid to non-performing assets in the banking system and the change in the methodology of their calculation. The defining problems of the development of bank lending are systematized and substantiated, taking into account the change in economic dynamics under the influence of the state of war: the liquidation of a significant number of banks; the unstable military-political and financial-economic situation, as well as the decrease in public trust in credit institutions, have a decisive influence on the modern development of lending in Ukraine; nominal growth of the volume of loans granted while reducing their volume in real terms; significant deterioration in the quality of loan portfolios of commercial banks of Ukraine; uncertainty of business and banking institutions; high level of credit dependence of enterprises in the pre-crisis period; high level of problem loans; inflation. Despite the difficult economic and political circumstances, the banking system continues to maintain stability. For its part, the National Bank of Ukraine introduced certain relaxations regarding the control over the activities of commercial banks, taking into account their activities in crisis conditions.